A bowl full of peace : a true story - Stelson, Caren Barzelay (Carolrhoda Books, 2020)
"Six-year-old Sachiko and her family suffered greatly after the atomic bombing of Nagasaki, and in the years that followed, the miraculous survival of a ceramic bowl became a key part of Sachiko's journey toward peace"--